From Boardrooms to Markets: Understanding the Influence of Governance, Structure on Stock Performance - Fatima, Aabroo; Jamil, Muhammad (Pakistan Journal of Humanities and Social Sciences, 2025)
The research aims to explore the relationships between structural dynamics, management and conduct within stock markets, external governance factors and stock market performance. We have collected secondary data of fifty-nine countries spanning from 1995 to 2021 have been studied. We have employed Fixed Effect Model and Arellano Bond Estimation accounting endogeneity concerns. The study concluded that previous year stock market performance is positively related with current year performance. Structure of stock markets, internal governance, individual using internet and external governance indicators except rule of law have positive and significant relation with stock market performance. Regulatory business environment, governance practices and easy access of knowledge to public improves the stock market performance. The study found that institutional quality, enhanced stability in politics and less corruption should be kept in prime focus by policy maker. Facilities like internet access make public more aware of stock market dynamics and improves the participation of public in stock markets. The previous year performance of market, result in an outlook which increase the expectations of investors for businesses and triggering further positivity in the market. This leads to anticipation regarding the trend that this behavior will continue, and it results in increasing returns. Findings of the research provide valuable insights for market regulators and policymakers seeking to promote stability in financial market and foster sustainable economic growth.